A Comparative Study of Pectin Green Extraction Methods from Apple Waste: Characterization and Functional Properties - Marwa Hanafy Mahmoud; Ferial Mohamed Abu-Salem; Dina El-Sayed Helmy Azab (International Journal of Food Science)
Traditional methods of pectin extraction led to drop quality, yield, functional properties, and excessive time. The objective of our research is to produce high-quality pectin from apple pomace as food processing by-product. Four nonconventional methods of extraction (microwave, ultrasound, citric acid, and organic acid mixture (citric acid, ascorbic acid, and acetic acid)) were compared to conventional extraction of pectin in terms of yields, thermal behavior, functional groups, antioxidant activity, and functional properties. Citric acid extraction method gave the highest yield (22%) compared to other methods. The extraction of pectin by organic acid mixture maximized the galacturonic acid index to 87.58%;. Also, it was changed from structural into: compacted, multilaminated, and flaky surface compared to the other samples (more porous and hollow opening structural) as well as increased stability of pectin particles in colloids as a result of increasing the charge on particles to -59.42, beside its higher thermal stability of pectin behaviors, which reflected on improving all functional properties compared to the other methods. On the other side, microwave-extracted pectin had the highest antioxidant activity (3-4 times) compared to other extraction methods. In conclusion, extraction using organic acids, microwave, and ultrasonic led to improve the pectin quality and could be used in high-temperature food products, like bakery products.